Chronic Migraine and Medication Overuse Headache Worsening After OnabotulinumtoxinA Withdrawn Due to the Severe Acute Respiratory Syndrome-Coronavirus-2 Pandemic - Baraldi, Carlo; Ornello, Raffaele; Favoni, Valentina; Sacco, Simona; Caponnetto, Valeria; Pierangeli, Giulia; Pani, Luca; Cevoli, Sabina; Guerzoni, Simona (Frontiers in Neurology, 2021)
Introduction OnabotulinumtoxinA (BT-A) is a preventive treatment for chronic migraine (CM), which needs to be administered regularly by a trained clinician every three month. The spread of the severe acute respiratory syndrome coronavirus-2 (SARS-COV-2) pandemic has forced many patients to momentarily stop the scheduled BT-A injections. The goal of this study was to explore whether those patients experienced a worsening of their CM and, if any, the clinical predictors of migraine worsening after BT-A withdrawal. Methods This was a retrospective, multi-center study. Patients’ clinical data were obtained from their clinical documentation stored at each center. In particular, the following variables were collected: the mean number of headache days in the last month (NHD), the average number of painkillers taken in the last month (AC), the average number of days in which patients took, at least, one painkiller in the last month (NDM), the average intensity of migraine using the numeric rating scale (NRS) score in the last month and the average score obtained at the 6-items Headache Impact Test (HIT-6). The abovementioned variables were compared before and after BT-A withdrawal. Results After BT-A suspension, there was a significant increase in the NHD (P=0.0313, Kruskal-Wallis rank test), AC (P=0.0421, Kruskal-Wallis rank test), NDM (P=0.0394, paired t-test), NRS score (P=0.0069, Kruskal-Wallis rank test) and HIT-6 score (P=0.0372, Kruskal-Wallis rank test). Patients who were not assuming other preventive treatments other than BT-A displayed similar results. Patients who experienced a >30% worsening in NHD after BT-A withdrawn displayed a longer CM history (P=0.001, Kruskal-Wallis rank test), a longer MOH duration (P=0.0017, Kruskal-Wallis rank test), a higher AC value at the baseline (P=0.0149 , Kruskal-Wallis rank test), a higher NDM (P=0.0024, ttest) and a higher average value of the NRS score (P=0.0073, Kruskal-Wallis rank test). Conclusion BT-A withdrawn during SARS-COV-2 pandemic was associated with a general worsening in patients suffering for CM, hence the need to continue BT-A injection, in order to avoid patients’ worsening.